Revenue and expenditure patterns of local authorities in Sarawak - Norhalimah, binti Hj. Mohamad Hamni (Universiti Malaysia Sarawak (UNIMAS), 2002)
Local authorities are the lowest hierarchy in the government level. They performed a wide range of municipal services and have adequate fund to carry out their duties efficiently and effective as they act as a facilitator of socio-economic growth. Management of financial aspect of local authority is crucial in order to survive and continuously served the local communities within the local area. Furthermore, efforts to strengthen the financial condition of local authorities need to be emphasized because planning for development within particular area by the Federal or State government is shouldered by local authorities. The 24 local authorities in Sarawak are chosen as a sample of the study. This study examines the trend or revenue and expenditure patterns among 24 local authorities look at the financial situations and explore the uneven structure or revenue and expenditure. The research is confined to secondary data, historical financial summaries of component revenue and expenditure data for all local councils for each of the preceding 10 years from 1991-2000. A time series analysis is applied to look at the patterns of revenue and expenditure and financial situations. "Longtitudinal" approach is also applied where the data collections for each local authority for a period of certain years are collected